2014
DOI: 10.1186/s13014-014-0248-9
|View full text |Cite
|
Sign up to set email alerts
|

Quality assurance for the EORTC 22071–26071 study: dummy run prospective analysis

Abstract: PurposeThe phase III 22071–26071 trial was designed to evaluate the addition of panitumumab to adjuvant chemotherapy plus intensity modulated radiotherapy (IMRT) in locally advanced resected squamous cell head and neck cancer. We report the results of the dummy run (DR) performed to detect deviations from protocol guidelines.Methods and MaterialsDR datasets consisting of target volumes, organs at risk (OAR) and treatment plans were digitally uploaded, then compared with reference contours and protocol guidelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 32 publications
(34 reference statements)
0
8
0
Order By: Relevance
“…A review on QA for radiotherapy in randomised trials showed that major protocol deviations were observed in 11.0-48.0% of all cases, and were reported to be associated with impaired overall survival and local control and potentially increased treatment related toxicity [15]. This has also been reported by several other investigators, emphasising that the design of the QA-procedure needs to be tailored to specific trial techniques and outcomes [20,22,23,[32][33][34].…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…A review on QA for radiotherapy in randomised trials showed that major protocol deviations were observed in 11.0-48.0% of all cases, and were reported to be associated with impaired overall survival and local control and potentially increased treatment related toxicity [15]. This has also been reported by several other investigators, emphasising that the design of the QA-procedure needs to be tailored to specific trial techniques and outcomes [20,22,23,[32][33][34].…”
Section: Discussionmentioning
confidence: 82%
“…Especially for radiotherapy trials in general, QA is considered essential as a decrease in therapeutic effectiveness and impaired trial outcomes by protocol deviations have been reported [15,16]. Furthermore, QA increases trial protocol adherence and treatment uniformity, and therewith ensures optimal treatment in both arms which leads to more reliable trial outcomes [17][18][19][20][21][22][23].…”
mentioning
confidence: 99%
“…Learning from the negative experience of the TROG 0202 study, the EORTC organized an extended "dummy run" for their phase III EORTC 22071-26071 study designed to evaluate the addition of panitumumab to adjuvant chemo-IMRT in locally advanced, resected squamous cell HNC (19,26) A computed tomography dataset comprising one case of NHC was sent to the participating institutions and then compared with reference contours and protocol guidelines by six central reviewers. Of the 23 datasets, 13% of the GTV (gross tumor volume = macroscopic disease), 44% of the CTV (clinical TV = zone of possible microscopic extension), and 57% of the PTV (planning TV = margin for movement and setup uncertainty) contours were evaluated unacceptable (objectives and constraints defined per protocol and taking into account all available information along with ICRU recommendations) by the expert panel.…”
Section: Importance Of Rt Qa In Clinical Trialsmentioning
confidence: 99%
“…While strict adherence to ICRU 83 guidelines on "Prescribing, Recording, and Reporting Intensity-Modulated Photon-Beam Therapy" can address most of the (QA) issues required to obtain adequate dose distribution during planning and delivery, work is still required to achieve consensus and QA of contouring (28). In addition to the study by Fairchild et al mentioned above, the PARSPORT study also found large differences in contouring in 3 out of 10 submissions due to lack of adherence to the trial guidelines (26,29). The Swiss national "dummy run" study found that more precise radiological imaging could increase homogeneity in delineation of the GTV (30).…”
Section: Importance Of Rt Qa In Clinical Trialsmentioning
confidence: 99%
“…is a trial‐specific benchmarking exercise to assess an institution's ability to understand and comply with trial protocol contouring and dosimetric requirements. A benchmarking exercise as part of QART has been reported for clinical trials involving many anatomical sites including head and neck, gynaecological and intact prostate . Matzinger et al .…”
Section: Introductionmentioning
confidence: 99%